The Influence of Environmental Concern, Convenience, and Trust on Purchase Decision: Mediating Role of Purchase Intention - Zebua, Alexander; Sijabat, Rosdiana (Universitas Negeri Semarang, 2025)
Environmental concerns and convenience in buying decisions are all significant aspects of influencing consumer purchasing decisions in the modern period. Hence, they must be addressed in fundamental marketing techniques. This Study sought to explain the direct influence of environmental concerns, convenience, trust, and purchase intention as mediating variables in the purchasing decision. The respondents in this study are SaladStop customers in Jakarta. This study's sample size is 160 respondents, selected using a purposive sampling technique and a Likert scale questionnaire using SmartPLS. This study's limitation is the quantity of sample only 160 respondents with only customers that ever consumed the product SaladStop. The study confirms that environmental concern, convenience, and trust have a positive and significant impact on purchase intention, and purchase intention has a positive and significant as mediating effect of trust on purchase decision.